Mechanical Behaviour Of Coir Fibre Reinforced With Polyester Composite - JAMALUDDIN, MUHAMMAD NUR FADHLIUDIN; HASHIM, MOHD YUSSNI (Research Progress in Mechanical and Manufacturing Engineering, 2022)
Coir fibres are commonly used in various industrial applications. The purpose of this research was to study the effect of alkali treatment and fibre content with different percentage on tensile and flexural strength of polyester resin reinforced by coir fibre. In this study, coir fibre were treated with sodium hydroxide (NaOH) concentration 5% for 24 hours at room temperature and dried for 48 hours. The coir fibre content was also varies from 10% and 20%. Hand lay-up method were used to fabricate the composite. Composite material is a material that consist of a combination with at least two or more constituent materials which have significance contrast chemical or physical properties. From the literature review, the treated coir fibre would increase the strength of the coir fibre reinforced with polyester composited compared to untreated coir fibre. The results from previous researcher shown that the fibre content in weight percentage and alkali treatment with suitable condition which is 5% of NaOH concentration are playing major role on the improvement of tensile strength and flexural strength